Investigating the Discharge Coefficient and Efficiency of the Pivot Side Weirs with Threshold - Hooman Kheybar; Seyed Mohsen Sajjadi; Javad Ahadiyan; Mehdi Ghomeshi (رویکردهای نوین در مهندسی آب و محیط زیست)
In this research, the flow coefficient and efficiency of the pivot side weir with the flow threshold under different opening angles towards the side channel were investigated. The weir model built in this research consists of a threshold part with a fixed right angle and an inclined hinge part with the ability to change the angle. the performance of three models with a ratio of 1.5, 1 and 0.75 were examined and their flow coefficient and efficiency were calculated. According to the laboratory results, it was observed that for all the numbers of the upstream landing, with the increase of the opening angle towards the side channel, the discharge coefficient of different models is on average about 30 to 60% and the efficiency is about 20 to 45% compared to the control model. rectangular weir with a sharp vertical edge) will increase. Next, a linear relationship was obtained in order to calculate the flow coefficient of the laboratory models. R^2 of this relationship is equal to 0.72 and the NRMSE and WQD error values for it were calculated as 0.6 and 0.02, respectively. The results of this research showed that the opening of the model facing the side channel under different angles leads to an increase in the flow coefficient and weir efficiency and will have a positive effect on the performance of the pivot side weir. By verifying the accuracy of the linear relationship obtained in this research, it can be concluded that the mentioned equation is accurate.